Fostering research skills in undergraduate medical students through Mentored Student Projects: Example from an Indian medical school - Devi, V; Abraham, R R; Adiga, A; Ramnarayan, K; Kamath, A (Kathmandu University Medical Journal, 2012)
Background Healthcare decision-making is largely reliant on evidence–based medicine; building skills in scientific reasoning and thinking among medical students becomes an important part of medical education. Medical students in India have no formal path to becoming physicians, scientists or academicians. Objectives This study examines students’ perceptions regarding research skills improvement after participating in the Mentored Student Project programme at Melaka Manipal Medical College, Manipal Campus, India. Additionally, this paper describes the initiatives taken for the continual improvement of the Mentored Student Project programme based on faculty and student perspectives. Methods At Melaka Manipal Medical College, Mentored Student Project was implemented in the curriculum during second year of Bachelor of Medicine and Bachelor of Surgery programme with the intention of developing research skills essential to the career development of medical students. The study design was cross-sectional. To inculcate the spirit of team work students were grouped (n=3 to 5) and each group was asked to select a research project. The students’ research projects were guided by their mentors. A questionnaire (Likert’s five point scale) on students’ perceptions regarding improvement in research skills after undertaking projects and guidance received from the mentor was administered to medical students after they had completed their Mentored Student Project . The responses of students were summarised using percentages. The median grade with inter-quartile range was reported for each item in the questionnaire. The median grade for all the items related to perceptions regarding improvement in research skills was 4 which reflected that the majority of the students felt that Mentored Student Project had improved their research skills. The problems encountered by the students during Mentored Student Project were related to time management for the Mentored Student Project and mentors. Results This study shows that students acknowledged that their research skills were improved after participating in the Mentored Student Project programme. Conclusions The Mentored Student Project programme was successful in fostering positive attitudes among medical students towards scientific research. The present study also provides scope for further improvement of the Mentored Student Project programme based on students’ and faculty perspectives. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6215 Kathmandu Univ Med J 2010;8(3):294-8